Epilepsy and Electroencephalographic Abnormalities in Children with Autistic Spectrum Disorder - İpek Polat; Ayşe Semra Hız; Uluç Yiş; Müge Ayanoğlu; Derya Okur; Erhan Bayram; Hüseyin Burak Baykara (Galenos Publishing House, 2022)
Objective: Epilepsy and electroencephalography (EEG) abnormalities are more commonly seen in autism spectrum disorder (ASD). The aim of the present study is determine the risk factors that cause epilepsy, seizures and EEG abnormalities in cases with EEG examination who were followed with the diagnosis of ASD. Method: A total of 166 cases diagnosed with ASD according to the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition in Dokuz Eylül University Faculty of Medicine Hospital Clinic of Child Psychiatry and whose neurological evaluations and examinations were performed in the pediatric neurology clinic, were included in the study. We retrospectively recorded and analyzed the cases' clinical features, the results of physical examination, imaging and EEG, comorbidities and medications they used. Results: Of the cases, 74.4% were male. The mean age of cases with epilepsy diagnosis, at least one seizure and epileptic discharges on EEG was higher (p<0.001, p<0.001 and p=0.005, respectively). The history of epilepsy and having at least one seizure were more common in cases aged 11 years and older (p=0.001 and p=0.001, respectively). Abnormalities in EEG examination and epileptic discharges were detected to be more common in female ASD cases (p=0.041 and p=0.019 respectively). Conclusion: In ASD cases without any underlying chronic neurological disease, female gender is a risk factor for the development of EEG abnormality and epileptic discharges. Advanced age is a risk factor for seizures and development of epilepsy in ASD cases.